Dos conflitos socioambientais à responsabilidade social corporativa: uma análise sobre a auto-regulação dos atores privados na governança global - D’Angelo, Flávia Pereira (2023)
In the last years, companies have been encouraged by their investors and consumers to include socio-environmental impact initiatives in their business strategies, so that Corporate Social Responsibility (CSR) has been an increasingly present discussion among the private sector. Despite the importance of companies engaging in this debate, many of the multinationals that claim to have a solid commitment to sustainability are also those that have played a leading role in socio-environmental conflicts, resulting from unbridled contamination and pollution of the environment, with local communities – especially in the Global South. The literature points out that CSR is, in many cases, a reaction of companies to the conflicts in which they are involved, whether to react to tensions or mitigate new social mobilizations. The purpose of this article is to analyze these two phenomena – private participation in local conflicts and its engagement in CSR – and problematize them in the context of global governance under the lens of selfregulation. It is argued that International Law does not have legal instruments to blame multinationals involved in conflicts in territories other than their country of origin, as well as there is still no public regulation of CSR at an international level. Therefore, it is concluded that CSR and the involvement of multinationals in conflicts are not opposing and contradictory practices, but mutually constitutive, as they are part of the same continuum of self-regulation by the private sector and the production of international norms